JAEPL, Vol. 7, Winter 2001-2002 - Linda T. Calendrillo, Editor; Kristie S. Fleckenstein, Editor (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
Morris Berman tells the story of his maternal grandfather, who, when he was five years old in 1883 or 1884, was sent to a Jewish elementary school in Belorussia. On the first day of class, the teacher startled the young boy by taking each child's slate and smearing the first two letters of the Hebrew alphabet—aleph and beys—on it in honey. His grandfather's first lesson consisted of eating the letters off the slate. The symbolism of this act is complex, Berman muses, but central to the ritual is the belief that what is real must be taken into oneself, ingested: "we literally eat the other, take it into our guts, and as a result are changed by it" (267-68). A similar, although usually unspoken, belief continues to weave through literacy teaching in this century, in this country. Writing and reading, all acts of rhetoric, involve "communication by the signs of consubstantiality, the appeal of identification," Kenneth Burke writes in A Rhetoric of Motives, and identification is "hardly other than a name for the function of sociality" (Attitudes 144). The quintessential word man who saw in language the poetic function of making, resonating to the original sense of the term poiesis, Burke tied our language and our making to our bodies. We are, after all, symbol-using animals, a definition that gives equal weight to body and language ("Definition" 3-9). The lure of language is that it offers us the means to bridge our separations from one another; we can become consubstantial, of one substance. We can engage, and through that engagement we can write and read for "tolerance and contemplation" (Rhetoric xv). The seven articles in this issue honor the call of engagement, of identification for "tolerance and contemplation," through sense-able teaching: teaching with the senses to the senses. We open with W. Keith Duffy who, in Imperfection: The Will-to Control and the Struggle of Letting Go, finds in a spiritual balance the ability to embrace the "essential role of imperfection" in the writing classroom. By engaging with our paradoxical and mixed-up natures, we can unite in meaningful ways. Randall Popken in Felt Sensing of Speech Acts in Written Genre Acquisition explores the necessary engagement of student writer and multiple texts as a means to evolve a felt sense of a new genre. Drawing on Eugene Gendlin's concept of felt sense, Popken traces the connection between the development of a physical, tacit sense of genre knowledge and the development of rhetorical expertise in that genre. While Popken shapes the growth of rhetorical expertise, Caroline Mancuso shapes the rhetorical value of growing pains in Teacher Growing Pains. By acknowledging and attending to "growing pains," what Dewey calls the "travail of thought" required to evolve a new perspective, readers and writers can grow in "wholeness individually and in community," Mancuso argues. The sense of growing into new thinking by allowing it to enter our souls is the focus of Dennis Young's A Poetics of Student Writing. The "poetics" of Young's title refers to the "soul-making, aesthetic dimension of student writing," a process that can be enacted only when we are actively involved with the making. Through an examination of student texts, Young promotes a "poetic basis of mind" in which students and teachers can foster an awareness of their own soul work. The necessity of engagement if further underscored by Dale Jacobs in Being There: Revising the Discourse of Emotion and Teaching, who argues that a teacher must be fully engaged in the classroom to create an atmosphere that fosters a student's intellectual, emotion, and physical growth. Inviting us into his experience of learning of to listen deeply to his students, Jacobs teaches us how to enact that same deep listening in our own literacy classrooms. Central to engagement is the quality of unity, a dissolution of a dualistic mind set. Marilyn Middendorf tackles the issues of dualism directly in Discredited Metaphors of Mind Limit Our Vision. Middendorf claims that metaphors of mind steeped in dualistic, hierarchical imagery undermine our effectiveness in the classroom. She offers us a different vision of mind based on the materialism of current neurological theories of the mind, a version that explodes the mechanic sender-receiver, information transfer model of communication for a one that foster the engagement of dialogic communication. The cognitive and somatic learning involved in dressage serves as the start for effective teaching for Lorie Heggie in Flow, Centering, and the Classroom: Wisdom from an Ancient Friend. Drawing on her experience in learning how to center while engaged in classical riding, Heggie explores how such experience enables her to center in her writing classroom and how such experience enables her to help her students center as well. This physical-intellectual process, Heggie argues, requires our immersion in the task at hand so that we are one with the task, drawn into the marvelous current of flow. We are symbol-using animals who find in language the means of identification, of consubstantiality, and the need for it. Can we do less in our classrooms that teach sense-ably for engagement? In the spirit of sense-able teaching and the importance of the myriad faces of engagement, we introduce a new section: Connecting. Consisting of teacher narratives and edited by Helen Walker, each contribution serves to connect us more fully to our students' growth and our own.
Keywords: Journal of the Assembly for Expanded Perspectives on Learning